Pengembangan Media Robot Malin Kundang Berbasis Pembelajaran Berdiferensiasi di Sekolah Dasar - Exsaris Januar (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2022)
Among the problems that occurred in class VI of SDN 44 Kalumbuk, Kuranji District, Padang City, West Sumatra Province, were the lack of concrete teaching aids to explain the process of the eclipse and the lack of implementation of differentiation learning. The purpose of this study was to determine the validity, effectiveness, and practicality of the Malin Kundang Robot media in integrated thematic learning in Grade VI Elementary School. The research used the ADDIE Development Research type (analysis, design, development, implementation, and evaluation). The results of the Malin Kundang Robot media test show that this media is valid, practical, and effective. The effectiveness of this media is evidenced by the increase in student learning outcomes from the average result of 68.57 to 83.33 after using the media.